Educational intervention to improve adherence to the Mediterranean diet among parents and their children aged 1–2 years. EniM clinical trial. Issue 6 (10th August 2015) - Roset-Salla, Margarita; Ramon-Cabot, Joana; Salabarnada-Torras, Jordi; Pera, Guillem; Dalmau, Albert
Abstract: Objective: The objective of the present study was to evaluate the effectiveness of an educational programme on healthy alimentation, carried out in day-care centres and aimed at the parents of children from 1 to 2 years of age, regarding the acquisition of healthy eating habits among themselves and their children. Design: We performed a multicentre, multidisciplinary, randomized controlled study in a community setting. Setting: The EniM study (nutritional intervention study among children from Mataró) was performed in twelve day-care centres in Mataró (Spain). Centres were randomized into a control group (CG) and an intervention group (IG). IG received four or five educational workshops on diet, CG did not have workshops. Subjects: Children, not exclusively breast-fed, from 1 to 2 years of age, in the participating day-care centres and the persons responsible for their alimentation (mother or father). Results: Thirty-five per cent of the IG did not attend the minimum of three workshops and were excluded. The CG included seventy-four children and seventy-two parents and the IG seventy-five children and sixty-seven parents. Both groups were comparable at baseline. Basal adherence to the Mediterranean diet was 56·4 % in parents (Gerber index) and 7·7 points in children (Kidmed test). At 8 months, Mediterranean diet adherence had improved in the IG by 5·8 points in the Gerber index ( P= 0·01) and 0·6 points in the Kidmed test ( P =0·02) compared with the CG. Conclusions: This educational intervention performed in parents at the key period of incorporation of a 1–2-year-old child to the family table showed significant increases in adherence of the parents to the Mediterranean diet, suggesting future improvement in different indicators of health and an expected influence on the diet of their children.